COMPARISON OF ANTERIOR TUBE THORACOSTOMY AND POSTERIOR TUBE THORACOSTOMY IN THE MANAGEMENT OF HEMOTHORAX - NAQVI , SMR; MATEEN , A; FARHAN , IA; SHAH , SMA (Biological and Clinical Sciences Research Journal, 2023)
Trauma to the chest occurs through blunt or penetrating injury and may lead to the development of hemothorax, pneumothorax, etc. Management of chest trauma involves surgical treatment such as tube thoracostomy. This study aimed to compare the evacuation of hemothorax after chest trauma by anteriorly and posteriorly placed chest tubes in terms of the requirement of any further invasive surgical intervention. One hundred thirty-two patients who fulfilled the inclusion criteria were enrolled and divided into two groups of equal number, i.e., 66 each. Patients in group A underwent anterior tube thoracostomy, and group B underwent posterior tube thoracostomy. All patients after the 7th post-op day of chest intubation had a chest x-ray and ultrasonography of the chest. Patients who had retained clotted hemothorax underwent further invasive surgical intervention. The mean age of the patients, duration of trauma, and duration of stay in the hospital in anterior vs. posterior thoracotomy were 35.48±10.34, 12.54±5.79 and 13.58±6.55 and 37.42±9.68, 14±6.27 and 9.45±3.4, respectively. 48.5% of patients needed secondary intervention in Group A, whereas 9% needed it in Group B. Comparison of both groups was done by Chi-square test, and a p-value of 0.000 was obtained. Posterior intubation was more effective compared to anterior tube thoracostomy in preventing the patient from further surgical intervention.